Handbuch Sprache in der Wirtschaft - Hundt, Markus; Biadala, Dorota; Jäschke, Daniel (Handbücher Sprachwissen, 2015)
Researchers in linguistics have long sought a concise, scientifically based synopsis of communication in economics and business. The handbook meets this need and covers the key areas of communication in economics (internal and external corporate communication and intercultural communication). Its target audience includes teachers, researchers, and students of linguistics.